GOVERNMENT ROLE IN ENHANCING MSME MARKET ACCESS AT REGIONAL AND GLOBAL LEVELS - Syafrida; Arihta Eshter Br Tarigan; Ema Farida (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are small-scale businesses and home industries that produce various products. Generally, they operate using simple methods, with minimal use of technology and limited capital, which hinders business growth. The government plays a role in fostering MSMEs, as they are the backbone of both community and national economies. MSMEs contribute to job creation. Given the importance of MSMEs and the challenges they face in running their businesses, government intervention is needed to provide support. This support includes facilitating access to business capital, licensing, and technology utilization for product marketing. The government also assists MSMEs in continuously improving quality and standards through product innovation to enhance competitiveness. Furthermore, fostering collaborations and partnerships with other countries, relevant institutions such as BPOM, the Ministry of Tourism and Creative Economy, BNSP, domestic and foreign investment companies, and higher education institutions is essential.